2020
DOI: 10.1177/0305735620958464
|View full text |Cite
|
Sign up to set email alerts
|

Spanish adaptation of a film music stimulus set (FMSS): Cultural and gender differences in the perception of emotions prompted by music excerpts

Abstract: The literature review reveals different conceptual and methodological challenges in the field of music and emotion, such as the lack of agreement in terms of standardized datasets, and the need for replication of prior findings. Our study aimed at validating for Spanish population a set of film music stimuli previously standardized in Finnish samples. In addition, we explored the role of gender and culture in the perception of emotions through music using 102 excerpts selected from Eerola and Vuoskoski’s datas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
46
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(51 citation statements)
references
References 68 publications
4
46
1
Order By: Relevance
“…As a consequence, the FMMS excerpts selected in the present study were previously edited by shortening them to 8 s in order to ensure a similar trial duration within the task, being therefore comparable to prior music studies (Gringas et al, 2015;Khalfa et al, 2002), as well as other works using emotional pictures or sounds in diverse paradigms such as passive viewing, aversive conditioning, or cognitive reappraisal tasks (Conzelmann et al, 2015;Fuentes-Sánchez et al, 2019;López et al, 2009). Thus, the first objective was to investigate the correspondence between the subjective ratings obtained in the a priori validation study-with longer and variable excerpts durations (Fuentes-Sánchez et al, 2020)-and those obtained here for the shortened excerpts. A second goal was to investigate the effect of music category (unpleasant, neutral, and pleasant music) on (a) peripheral physiology (EDA, HR changes, zygomatic, and corrugator)-analyzing both specific parameters such as peak response or averaged activity and the time course across half-seconds bin; and (b) subjective ratings-both for affective dimensions (valence, energy, and tension arousal) as well as discrete emotions (happiness, anger, fear, tenderness, and sadness).…”
Section: Fuentes-sánchez Et Almentioning
confidence: 97%
See 1 more Smart Citation
“…As a consequence, the FMMS excerpts selected in the present study were previously edited by shortening them to 8 s in order to ensure a similar trial duration within the task, being therefore comparable to prior music studies (Gringas et al, 2015;Khalfa et al, 2002), as well as other works using emotional pictures or sounds in diverse paradigms such as passive viewing, aversive conditioning, or cognitive reappraisal tasks (Conzelmann et al, 2015;Fuentes-Sánchez et al, 2019;López et al, 2009). Thus, the first objective was to investigate the correspondence between the subjective ratings obtained in the a priori validation study-with longer and variable excerpts durations (Fuentes-Sánchez et al, 2020)-and those obtained here for the shortened excerpts. A second goal was to investigate the effect of music category (unpleasant, neutral, and pleasant music) on (a) peripheral physiology (EDA, HR changes, zygomatic, and corrugator)-analyzing both specific parameters such as peak response or averaged activity and the time course across half-seconds bin; and (b) subjective ratings-both for affective dimensions (valence, energy, and tension arousal) as well as discrete emotions (happiness, anger, fear, tenderness, and sadness).…”
Section: Fuentes-sánchez Et Almentioning
confidence: 97%
“…Furthermore, each shape represents the specific emotion that characterizes each musical excerpt. Crosses represent happiness excerpts; rhombus represents sad clips; red points represent fearful excerpts; pink points represent anger excerpts; and stars represent the excerpts that convey both anger and fear in a similar way with a cross presented in the center of a black screen during 1 s of silence baseline, followed by the presentation of unpleasant, neutral, or pleasant musical excerpts during 8 s. Afterward, participants rated different affective dimensions (valence, energy arousal, and tension arousal) and discrete emotions (happiness, sadness, tenderness, fear, and anger) using a 9-point scale as in the validation study (see Fuentes-Sánchez et al, 2020). Thereupon, familiarity was evaluated using a 3-point scale (0 = unfamiliar; 1 = somewhat familiar; and 2 = very familiar).…”
Section: Unpleasantmentioning
confidence: 99%
“…An analysis of subjective ratings indicated that all targeted emotions were significantly well discriminated, with a strong congruence between the two models (Eerola & Vuoskoski, 2011). The original FMSS results were obtained using a Finnish population (Eerola & Vuoskoski, 2011), and were recently replicated and validated in a Spanish population (Fuentes-Sánchez, Pastor, Eerola & Pastor, 2020).…”
Section: Introductionmentioning
confidence: 86%
“…Cada punto de la figura representa un fragmento musical (N = 110). (Eerola & Vuoskoski, 2011;Fuentes-Sánchez et al, 2020) on the basis of their mean valence (x-axis) and energy arousal (y-axis) ratings (left), and on the basis of their mean valence (x-axis) and tension arousal (y-axis) ratings (right). (Eerola & Vuoskoski, 2011;Fuentes-Sánchez et al, 2020) on the basis of their mean valence (x-axis) and energy arousal (y-axis) ratings.…”
Section: íNdice De Figurasmentioning
confidence: 99%
See 1 more Smart Citation